What's left of the left Democrats and Social Democrats in challenging times - Cronin, James E.; Ross, George 1940-; Shoch, James (Duke University Press, 2011)
Social democracy's past and potential future / Sheri Berman -- Historical decline or change of scale? The electoral dynamics of European social democratic parties, 1950-2009 / Gerassimos Moschonas -- Once again a model : Nordic social democracy in a globalized world / Jonas Pontusson -- Embracing markets, bonding with America, trying to do good : the ironies of New Labour / James Cronin -- Reluctantly center-left? The French case / Arthur Goldhammer and George Ross -- The evolving democratic coalition : prospects and problems / Ruy Teixeira -- Party politics and the American welfare state / Christopher Howard -- Grappling with globalization : the Democratic Party's struggles over international market integration / James Shoch -- European center-left parties and new social risks : facing up to new policy challenges / Jane Jenson -- Immigration and the European left / Sofía Pérez -- The Central and Eastern European left : a political family under construction / Jean-Michel De Waele and Sorina Soare -- European center-lefts and the mazes of European integration / George Ross
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte 1970-2010; Political parties / History / United States; Political parties / History / Europe; Right and left (Political science); Globalization / Political aspects; Wirtschaftsentwicklung; Sozialer Wandel; Sozialdemokratie; Globalisierung; Europa; USA; Aufsatzsammlung